2021
DOI: 10.3390/atmos12060738
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Point Clouds from Automotive Lidars Exposed to Artificial Rain and Fog

Abstract: Light Detection And Ranging sensors (lidar) are key to autonomous driving, but their data is severely impacted by weather events (rain, fog, snow). To increase the safety and availability of self-driving vehicles, the analysis of the phenomena of the consequences at stake is necessary. This paper presents experiments performed in a climatic chamber with lidars of different technologies (spinning, Risley prisms, micro-motion and MEMS) that are compared in various artificial rain and fog conditions. A specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
3
15
0
Order By: Relevance
“…They declared that all the tested sensors' performance decreased in harsh weather, and it is difficult to say which one is better. Karl et al [104] analysed the intensity and the number of points detected on a calibrated target and in the frustum between the sensor and the target in artificial fog and rain with the LiDARs of Velodyne, Ouster, Livox, Cepton, and AEye in different echo modes. They found that the 1550nm AEye LiDAR allows better quality of point clouds, and a non repetitive scan pattern from the Livox LiDAR shows good performances under fog.…”
Section: Adverse Weather Conditionsmentioning
confidence: 99%
“…They declared that all the tested sensors' performance decreased in harsh weather, and it is difficult to say which one is better. Karl et al [104] analysed the intensity and the number of points detected on a calibrated target and in the frustum between the sensor and the target in artificial fog and rain with the LiDARs of Velodyne, Ouster, Livox, Cepton, and AEye in different echo modes. They found that the 1550nm AEye LiDAR allows better quality of point clouds, and a non repetitive scan pattern from the Livox LiDAR shows good performances under fog.…”
Section: Adverse Weather Conditionsmentioning
confidence: 99%
“…The former is defined by the installed components (i.e., laser) and is reflected in the sensor specifications (i.e., range at 10% remission). Regarding environmental influences, precipitation and visibility (e.g., fog) are named in most cases, which limit the maximum range of the sensors [33,34]. Furthermore, the point density for the detection of an object is influenced by the angle between the object and the LiDAR sensor, due to the angular resolution of the device.…”
Section: Derivation Of Berthing Support Area (Bsa)mentioning
confidence: 99%
“…In this we will consider the possible illumination of vessels based on the sensor specification and setup. The influence of environmental conditions on LiDAR sensors is difficult to estimate and depends on the sensor model [34]. Therefore, the influence of weather is difficult to measure, and we have too little information to consider this for the BSA.…”
Section: Derivation Of Berthing Support Area (Bsa)mentioning
confidence: 99%
“…Recent studies have focused on the analysis of a specific noise factor on a sensor type, e.g. rain on LiDAR [4], [5], interference on RADAR [6], [7], fog on camera [8]. However, further investigation of noise factors is required, as the automotive environment is highly complex, swiftly changing, and multiple noise sources can impact the sensor outputs simultaneously.…”
Section: Introductionmentioning
confidence: 99%